Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.ijpddr.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and functional analyses reveal pleiotropic action of the anti-tumoral compound NBDHEX in Giardia duodenalis

Abstract: Giardiasis, a parasitic diarrheal disease caused by Giardia duodenalis, affects one billion people worldwide. Treatment relies only on a restricted armamentarium of drugs. The disease burden and the increase in treatment failure highlight the need for novel, safe and well characterized drug options. The antitumoral compound NBDHEX is effective in vitro against Giardia trophozoites and inhibits glycerol-3-phosphate dehydrogenase. Aim of this work was to search for additional NBDHEX protein targets. The intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 61 publications
6
31
0
Order By: Relevance
“…Experimental evidences suggest that NBDHEX can tightly bind to gTrxR in its oxidized fluorescent form, also in the absence of NADPH, likely by cysteine attack at two different drug positions (C4 and C6) of the bicyclic system. We also observed that the binding and enzyme inhibition follows a biphasic behavior [6]. Adducts between the nitro-reduced form of the drug and, mainly, the catalytic Cys137 and Cys140 of gTrxR could be detected by mass spectrometry analysis but only when NADPH was present [6].…”
Section: Interaction Of Nbdhex With Gtrxrmentioning
confidence: 82%
See 4 more Smart Citations
“…Experimental evidences suggest that NBDHEX can tightly bind to gTrxR in its oxidized fluorescent form, also in the absence of NADPH, likely by cysteine attack at two different drug positions (C4 and C6) of the bicyclic system. We also observed that the binding and enzyme inhibition follows a biphasic behavior [6]. Adducts between the nitro-reduced form of the drug and, mainly, the catalytic Cys137 and Cys140 of gTrxR could be detected by mass spectrometry analysis but only when NADPH was present [6].…”
Section: Interaction Of Nbdhex With Gtrxrmentioning
confidence: 82%
“…The full-length coding sequence of TrxR from the isolate WB-C6 of Giardia duodenalis (gTrxR, GL50803_9827) was cloned and expressed as N-terminal 6XHIS tagged protein in E. coli M15 strain as previously reported [6]. HIS-gTrxR was affinity purified on native condition on Ni-NTA Agarose (Qiagen, Germany) and eluted with 250 mM imidazole according to the manufacturer.…”
Section: Expression and Purification Of The Recombinant Proteinmentioning
confidence: 99%
See 3 more Smart Citations